The Role of Nursing Leadership in Health Services Accreditation - Lisnawati, Ni Made Ary; Suasnawa, I Gede; Widnyani, Ni Made; Sriwahyuningsih, Ni Luh Gde Nita; Darmayanti, Ni Luh (GLOBAL HEALTH SCIENCE GROUP, 2024)
Law Number 17 of 2023 concerning Health states that every health service facility is obliged to continuously and sustainably improve the quality of health services, one of which is by means of accreditation. Accreditation is a recognition of service quality.The success or failure of health service facilities in achieving accreditation goals is very dependent on the leadership's ability to improveCommitment from nurses in implementing accreditation in health services. This research design uses a scoping review, with 8 articles published from 2019-2024 in English or Indonesian, as well as complete articles. The literature review protocol and evaluation uses the PRISMA checklist to determine the selection of studies that have been found and adapted to the objectives of the literature review. Accreditation has a positive impact on the quality of health services in health service facilities. The role of nursing leaders has an important meaning in implementing accreditation. The role of nursing leaders has an important meaning in implementing accreditation in health service facilities. The ability of leaders to foster a sense of commitment from nurses plays a role in implementing accreditation in health services.